Malpractice Premiums and the Supply of Obstetricians - Daniel Polsky; Steven C. Marcus; Rachel M. Werner (SAGE Publishing, 2010)
Using longitudinal data on practicing obstetricians from 1998 to 2004 derived from Pennsylvania, Florida, and New York hospital discharge data, this study finds that rising malpractice premiums are associated with an increased rate of exit and a reduced rate of entry for obstetricians. In Pennsylvania and Florida, where premiums rose by an average of 20% per year for four years, the combined effect of more exits and fewer entries was associated with a decline in obstetrical labor supply of 80 physicians, or 5.3% of the supply of obstetricians.